Strengthening the Theoretical of Geotourism: A Systematic Literature Review - Sihotang, Doni Sugianto; Suhud, Usep; Handaru, Agung Wahyu (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
Over the past two decades, geotourism and geoheritage have gained increasing recognition as essential components of sustainable tourism and geological heritage conservation. Nevertheless, most existing reviews remain limited to site inventories or mapping publication trends. Few studies have engaged deeply with theoretical and conceptual frameworks across disciplines, and the research landscape continues to be dominated by work conducted in Europe and East Asia. This study aims to systematically examine how theoretical frameworks have been applied in geotourism and geoheritage research, while also analyzing the geographical distribution of publications to identify opportunities for advancing knowledge in the Global South. The research employed a systematic literature review following the PRISMA 2020 protocol. Scopus served as the primary database, yielding 718 records at the identification stage. After screening and applying inclusion and exclusion criteria, a total of 43 articles were included in the final analysis. The findings reveal that most studies continue to emphasize geosite inventories and geoheritage assessments, whereas the application of behavioral theories, conceptual models, and interdisciplinary approaches remains limited. Geographically, the literature is heavily concentrated in Europe and East Asia, with Southeast Asia, Africa, and Latin America remaining underrepresented. This study contributes by highlighting conceptual and spatial gaps that have not been comprehensively addressed in prior reviews. The implications suggest the need for stronger theoretical foundations and expanded research in the Global South to promote a more inclusive and globally sustainable development of geotourism.